Growing up laughing [large type] : my story and the story of funny - Thomas, Marlo (Thorndike Press large print biography, 2010)
The award-winning actress and #1 "New York Times"-bestselling author shares her funny and heartwarming stories of a life filled with laughter. Woven throughout the book are her interviews with America's most beloved comedians about how they, too, found the funny in their lives.